Evidence for Implicit—But Not Unconscious—Processing of Object-Scene Relations - Biderman, Natalie; Mudrik, Liad (Psychological science, 2018)
Is consciousness necessary for integration? Findings of seemingly high-level object-scene integration in the absence of awareness have challenged major theories in the field and attracted considerable scientific interest. Lately, one of these findings has been questioned because of a failure to replicate, yet the other finding was still uncontested. Here, we show that this latter finding—slowed-down performance on a visible target following a masked prime scene that includes an incongruent object—is also not reproducible. Using Bayesian statistics, we found evidence against unconscious integration of objects and scenes. Put differently, at the moment, there is no compelling evidence for object-scene congruency processing in the absence of awareness. Intriguingly, however, our results do suggest that consciously experienced yet briefly presented incongruent scenes take longer to process, even when subjects do not explicitly detect their incongruency.